Penataan Sarana Kelas dalam Mendukung Proses Pembelajaran di SMA Negeri 1 Tanjung Batu Kabupaten Ogan Ilir - Alpika, Nuralisa; Setyaningsih, Kris; Ibrahim, Ibrahim; Fatmawaty, Fatmawaty (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the arrangement of classroom facilities in supporting the learning process at SMA Negeri 1 Tanjung Batu Ogan Ilir. The type of qualitative research with a descriptive approach. There were 4 informants, with data collection methods through interviews, observations and documentation. Data analysis techniques through data collection, presentation and verification and conclusions. Data validity checking techniques through triangulation. The results and discussions stated that the arrangement of classroom facilities at SMA Negeri 1 Tanjung Batu Ogan Ilir had been carried out quite well, namely the availability of adequate learning facilities in each class, orderly and comfortable room arrangement for students, and the use of facilities such as whiteboards, LCD projectors, and other learning equipment that support the learning process. This arrangement provides a conducive learning atmosphere and increases student involvement in teaching and learning activities.